2021
DOI: 10.7717/peerj-cs.565
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional neural network-based ensemble methods to recognize Bangla handwritten character

Abstract: In this era of advancements in deep learning, an autonomous system that recognizes handwritten characters and texts can be eventually integrated with the software to provide better user experience. Like other languages, Bangla handwritten text extraction also has various applications such as post-office automation, signboard recognition, and many more. A large-scale and efficient isolated Bangla handwritten character classifier can be the first building block to create such a system. This study aims to classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Moreover, Animesh et al has come with a new architecture to identified isolated character and digit [11]. Similarly, Mir et al demonstrated ensemble approach on CNN model [12]. Nevertheless, we observed that these works, in particular, did not address the difficult small unit.…”
Section: Related Workmentioning
confidence: 78%
“…Moreover, Animesh et al has come with a new architecture to identified isolated character and digit [11]. Similarly, Mir et al demonstrated ensemble approach on CNN model [12]. Nevertheless, we observed that these works, in particular, did not address the difficult small unit.…”
Section: Related Workmentioning
confidence: 78%
“…This is followed by a global average pooling layer. After that, the densely connected layers are added where the last one being the output layer [62]. In the Xception architecture, all convolution and separable convolution layers are followed by batch normalization layer.…”
Section: The Proposed Ameliorated Xceptionnet Methodsmentioning
confidence: 99%
“…After the last block, there are two separable conv followed by a global average pooling (GAP) layer. After that, the fully connected (FC) layers are added with the last being the output layer" [23]. The Architecture of Xception model is shown in Fig.…”
Section: Xception Architecturementioning
confidence: 99%
“…Additionally, the presence of a global average pooling layer in place of a fully connected layer in the Xception model helps in preventing the problem of overfitting . [23]. Some modifications to the Xception architecture were made in two phases:…”
Section: Xception Architecturementioning
confidence: 99%